Comparison of Morning Heart Rate Variability at the Beginning and End of a Competition Season in Elite Speed Skaters - Taro Iizuka; Michihiro Kon; Taketeru Maegawa; Jun Yuda; Toru Aoyanagi; Hideyuki Takahashi; Tomoaki Atomi; Miho Shimizu; Yoriko Atomi (MDPI AG, 2020)
The aim of this study was to clarify whether the physiological fatigue status of elite speed skaters is influenced by the approximately five-month international competition season by comparing morning heart rate variability (HRV) at the beginning of the competition season (Japan Single Distances Championships: JSDC) with that at the end of the competition season (World Single Distances Championships: WSDC). Five international-class speed skaters participated in the study. HRV indices and subjective fatigue were measured each morning of the four days prior to the first races of the JSDC and WSDC in the 2007/2008 season. The parasympathetic HRV indices: root mean square of the successive R-R interval differences (RMSSD) (JSDC, 61.0 ms; WSDC, 42.1 ms; p < 0.05), high-frequency component power (HF) (JSDC, 1393 ms2; WSDC, 443 ms2; p < 0.05), and normalized unit of HF (HFnu) (JSDC, 53.2%; WSDC, 25.5%; p < 0.05) were lower for the WSDC than for the JSDC. The decrease in these indices may reflect the skaters' accumulated fatigue during the course of the competition season. Morning measurements of HRV may thus be an efficient way for elite speed skaters and coaches to objectively monitor physiological fatigue throughout the competition season.